THE ROLE OF THE PRINCIPLE IN THE INTEGRATION OF TECHNOLOGY AND HUMAN RESOURCES FOR OPTIMISING LEARNING AT SD MATARAM BARU - Bambang Yuswanto; Muhammad Ihsan Dacholfany; Sutrisni Andayani (International Journal of Teaching and Learning, 2025)
The development of information and communication technology demands the integration of technology in learning in elementary schools. This study aims to analyze the role of school principals in integrating educational technology and human resource management (HR) for learning optimization in elementary schools in Mataram Baru District, Lampung. This study uses a qualitative approach with a case study method in six elementary schools. Data collection techniques include interviews, observations, and documentation studies, analyzed using Miles and Huberman's interactive analysis model. The results of the study show that school principals play the role of strategic planners, drivers of digital learning innovation, managers of technological resources, facilitators of teacher training, and evaluators of technology use. The main challenges faced include limited infrastructure, low teacher competence, and resistance to change, which are addressed through collaborative approaches and the development of learning communities. This research enriches the concept of technology-based innovative leadership and offers an adaptive HR development model to support digital transformation in elementary schools.